State Regulation of the Salt Industry on the Astrakhan Salt Lakes in the First Half of the 19th Century - Taisiya Yudina; Marina Khairlapova (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения)
Introduction. Based on the materials of the State Archive of the Astrakhan region, which were first introduced into scientific circulation, the issues of salt extraction by the Kalmyks and its transportation by state peasants and Tatars on the Astrakhan salt lakes in the first half of the 19th century are highlighted. Methods and materials. The research is based on both published and unpublished sources. Analysis. The role of the state in organizing the selection of salt lakes, determining the amount of salt extracted and its transportation, hiring labor, remuneration, catering, and supply issues is analyzed. It was revealed that in the Astrakhan province, in addition to state-owned salt extraction, work was carried out on lakes owned by private salt producers, with the mandatory conclusion of a contract with the Astrakhan Salt Board and their payment of excise duty. Attention is focused on the rules developed by the Astrakhan Commission of Kalmyk Affairs for Kalmyks who were employed in government and private jobs. Results. Increased centralization and regulation of the organization of the salt business on the salt lakes of the Astrakhan province by the state was expressed in the identification of specific lakes for salt extraction, the organization of labor for its extraction, storage, and transportation, the establishment of wages, the price of sold salt, and the attraction of salt industrialists. It was aimed at increasing the Treasury’s income from the extraction and sale of Astrakhan salt. The contribution of the authors. Identification, collection, and processing of documents from the State Archive of the Astrakhan region were carried out by M.M. Khairlapova; preparation of sections of the article; and analysis of the process of organizing the salt industry by T.V. Yudina.